ARQUIVAR A VIDA: UMA POSSIBILIDADE PARA O ENSINO DE HISTÓRIA - Geyso Dongley Germinari (Universidade do Oeste de Santa Catarina, 2012)
The current article looks into the problem of using historical documents found infamily files. Such files are composed by photographs, birth certificates, invoices,working papers among other historical sources kept in drawers and in house cabinetsor cuddies. Using that theme as starting point, the research sought to understand thepossibilities and limitations offered by the use of family files in the history-teachingof primary-school-first-grade classes. In order to achieve that goal, a field-researchwas carried out with two primary-school teachers from Pinhais (a city in the surroundingarea of Curitiba, the capital city of the State of Paraná Brazil.) The researchmethodology was based on the interpretive/qualitative research applied to education,which served as guide for the collection of data, which, in turn was done by means ofproceeding with observations made during the class-preparation time and throughinterviews with the teachers. The results enabled to set up indicators in order to createa methodology of history-teaching for the first grades of primary-school focused onhistorical documents obtained from family files.